Pyrolytic studies of organic components in Antarctic carbonaceous chondrites Y-74662 and ALH-77307 - Murae, Tatsushi; Masuda, Akimasa; Takahashi, Takeyoshi (1984)
P(論文) The organic components of two Antarctic carbonaceous chondrites, Y-74662 (C2) and ALH-77307 (C3), have been investigated by pyrolysis using a Curie point pyrolyzer equipped with GC or GC-MS. Although a number of aromatic compounds have been detected as the pyrolysis products of Y-74662 along with a small amount of n-alkanes, only a few aromatic compounds in small quantities and no n-alkane have been detected in the components produced on the pyrolysis of ALH-77307. departmental bulletin paper